Sex Workers' Work-Related Victimisation and Drug Use During the First Year of the COVID-19 Pandemic in Switzerland - Molnar, Lorena (2022)
Criminologists have monitored the coronavirus pandemic’s effects on crime and criminal justice since the pandemic’s outbreak. Nonetheless, vulnerable and difficult-to-reach populations have been understudied thus far. This study sheds light on the experiences of sex workers (SW) during the first year of the coronavirus in Switzerland, a country where prostitution is legal. Based upon 40 questionnaires with SW outdoors and indoors and 50 h of field observation, SW reported that the pandemic has had adverse financial and psychosocial effects on them. During the first year of COVID-19, seventeen SW were victims of at least one work-related offence, the most prevalent of which were theft and fraud. Nevertheless, most SW did not report the incidents to the police. Comparing the non-victims with victims, we found that victims, particularly those of multiple crimes, are younger, more often foreigners from extra-EU countries, in an illegal situation and needed to work face to face during the prostitution ban during the lockdown in Switzerland. However, despite these circumstances, most SW do not use illegal drugs, and only a few of them used more during the pandemic. Our research findings were similar to those reported in former studies, although we could infer that the violent victimisation of our sample is less and none of the SW indicated violence on the part of the police. Nevertheless, we have no point of comparison with former years and thus propose a periodic crime victim survey of SW, as well as further prevention measures in the prostitution area